Scientific Evidence in Child Physical Abuse Prosecutions: A Case Study of Indonesia's Juvenile Court - Wewe Suryani; Herlita Eryke; Marlis Tarmizi (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The use of scientific evidence in proving child physical abuse remains underutilized in many juvenile justice systems, including Indonesia, where forensic proof such as visum et repertum and expert testimony is often not optimally integrated into judicial reasoning. This study aims to analyze the position and contribution of forensic evidence in the adjudication of child abuse cases, focusing on how such evidence supports the application of restorative justice and the principle of the best interest of the child. Using a normative-empirical legal method, this research examines positive legal provisions, court documents, and forensic reports, with a particular case study of Decision Number 13/Pid.Sus-Anak/2025/PT Bengkulu. The findings reveal that forensic evidence serves as a primary instrument for assessing the degree of injury and establishing the causal link between the perpetrator’s act and the victim’s medical condition. The application of scientific evidence enhances the objectivity and accuracy of judicial considerations, enabling judges to impose conditional sentences and social training rather than imprisonment. This demonstrates that legal forensics not only functions as a formal tool of proof but also as a moral and scientific foundation for restorative justice in child protection. The novelty of this study lies in its empirical demonstration that forensic evidence can bridge the gap between medical facts and legal decisions, promoting a more humane, rational, and knowledge-based juvenile justice system. Consequently, stronger collaboration among forensic institutions, correctional social workers, and child protection agencies is urgently required to ensure the consistent and effective use of scientific evidence in child abuse prosecutions in Indonesia.